Analisis Hubungan Pengetahuan dengan Perilaku Berisiko pada Pekerja di PT Elnusa Tbk - Hafiz Hidayat; Rahmi Pramulia Fitri; Dwi Sapta Aryantiningsih; Suryani Suryani (Science: Indonesian Journal of Science, 2025)
Data from the International Labour Organization (ILO) reveals that more than 2.3 million deaths due to work-related accidents and diseases occur each year worldwide. Additionally, there are approximately 374 million cases of non-fatal work-related accidents that directly impact labor productivity and company operations. Human error is identified as the dominant cause of workplace accidents in many industries, as reported by the National Occupational Safety and Health Agency of Indonesia (BKKBNI) in 2023, where 60% of accidents were caused by unsafe worker behavior. This study employs a descriptive quantitative approach aimed at describing and analyzing the relationship between the level of competence in the implementation of occupational health and safety (K3) and the working conditions of workers at PT Elnusa Tbk. This approach allows the researcher to perform numerical measurements of the variables studied and systematically and objectively interpret the data (Sugiyono, 2021). The research is planned to be conducted over six months, from February to July 2025. The sample size for this study consists of 30 workers. Based on the research results, 24 individuals (80.0%) exhibited non-risky behavior, while 6 individuals (20.0%) displayed risky behavior. Bivariate analysis indicated a statistically significant relationship between knowledge of risks, procedures, and the use of personal protective equipment (PPE) and workers’ risky behavior. The company is advised to continue strengthening its occupational safety education programs on a regular basis. Comprehensive and practical training should be provided, especially to workers with low levels of knowledge. Special thanks to the research location and IKes Payung Negeri for providing the opportunity for the researcher to conduct this study.